Influencia del sedentarismo en la calidad de vida de la gerontología del barrio Quito del cantón Santa Rosa en el año 2012 - Matamoros Apolo, Nelson Willam (2013)
In conducting fieldwork, where the need to perform recreational physical activities to combat physical inactivity, prior to diagnosis and recommendations of professionals trained in the area, developing a plan recreational activities with the involvement and participation of an interdisciplinary team was evident physical education teachers, doctors, psychologists, geriatricians and others in order to overcome the problem.